Effectiveness of Subsurface Flow-Wetlands to Reducing TSS Levels and Stabilizing pH in Tofu Liquid Waste - Endang Srilestari; Anita Munawwaroh (Jurnal Biologi Tropis, 2021)
Small and medium industries are experiencing growth every year. The home industry of tofu production is one of the small and medium industries that continues to grow and develop. However, there is a problem if the tofu production waste is disposed of directly into the waters, it will cause pollution due to the deposition of organic material. The research objective was to analyze the subsurface flow-wetlands with plants namely water hyacinth, apu wood and lemna minor to reducing TSS levels and stabilizing pH. This research an experimental with treatments including SSF-Wetlands without water plants (A1), SSF-Wetlands with water hyacinth (A2), SSF-Wetlands with apu wood (A3), SSF-Wetlands with lemna minor (A4) and SSF-Wetlands with water hyacinth, and apu wood (A5). The stages of this research are the sampling stage, the SSF-Wetlands manufacturing stage, the waste treatment stage and the pH and TSS testing stages. Data were analyzed using one-way ANOVA (SPSS 20). The results showed that the liquid waste of tofu in the initial sample was acidic, namely 3.94 and the TSS level was 858 mg / L. The pH condition of the waste after processing by the quality standard. ÃÂ The highest increase in pH and decrease in TSS levels in the tofu liquid waste treatment was the SSF-Wetland processing with water hyacinth plants (A2). This shows that water hyacinth plants have a greater role in neutralizing pH and can absorb the most suspended matter compared to apu wood and lemna minor plants.